Principals’ Perceptions of Ideal Counsellor Role - Hassard, J. Harvey; Costar, James W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The literature indicates that secondary school principals are significant determiners of counsellor role. Tension between principals and counsellors is not from day-to-day function but from differences in basic roles. In terms of priority, principals' primary concern is the institution, and secondary concern is the individual. Thus conflict in role but not duty or function may be built into the situation. Principals' expectations of secondary school counsellors include administrative support, information source, effective relationships and delivery of guidance services. Principals favour counsellors serving as facilitators of educational and vocational planning, as consultants, and as administrative agents. It is crucial that principals, counsellors and teachers understand their respective roles through negotiation and cooperation in order to maximize the learning process.